Les Associations D’entraide D’indigènes En Côte D’ivoire Coloniale 1937-1960 - Alexis Dea, Dr Lékpéa (International Journal of Scientific Research and Management (IJSRM), 2022)
Relations between settlers and colonized in the colony of Côte d'Ivoire have long been marked by mutual distrust and the total domination of the former, namely the settlers over the Indigenous Ivorians. Many frustrations suffered by the latter finally led them to organize themselves to ensure their survival on their own territory now confiscated by the French colonizer. One of the frameworks of this organization was the mutual aid association which appeared in 1924. If the objective of the first indigenous associations was to create a climate of solidarity and mutual aid in a society under strong foreign domination, gradually, these associations are transformed into real trade union and political protest movements. This article, produced on the basis of archival documents and information from various works on the colonial history of Côte d'Ivoire, is a contribution to the study of the social and particularly community life of the Indigenous peoples in the colony of Ivory Coast.